Analysis of Information Systems in Polish Companies and the Realization of the Business Intelligence Concept - Dudycz, Helena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
A management staff s need to gain necessary information in a certain period of time, in order to make the best decisions requires employing analytical applications of data processing based on a data warehouse. The architecture of an information system which contains the above-mentioned software allows the realization of the Business Intelligence (BI) concept. The aim of the following article is to analyze the state of implementation of information technology solutions which enable the multidimensional analysis of data in selected Polish companies in order to identify the possibilities of implementing the BI concept. Firstly, four interpretational approaches of implementing the BI concept are presented in order to guarantee the clarity of the deliberations. Subsequently the information technology solutions essential to the BI concept are discussed. An analysis of the results of the study conducted in Polish companies concludes the article and regards the implementation of transaction processing systems which operate the basic range of activity of the examined companies, data warehouses, analytical tools and corporate portal concerning the realization of the BI concept within them.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 40-48